2020
DOI: 10.1016/j.molstruc.2020.127975
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of crystal field effects and interactions using X-ray restrained ELMOs

Abstract: The purpose of this study is to assess the capability of X-ray restrained molecular wavefunction methods to reproduce the perturbation due to the crystal field. The effect of the crystal environment on the molecular charge densities has been thoroughly investigated experimentally and theoretically. However, the same analysis in terms of molecular orbitals is unprecedented. We specifically analysed the extremely localized molecular orbitals (ELMOs) because they allow for a valence bond like interpretation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…The option to study crystal field effects is also considered by Ernst et al (2020). These effects are found to be subtle, as shown previously by Bučinský et al (2019), but important (Ernst et al, 2020). This indicates the capability of XCW to transfer information from structure factors to the XC wavefunction (XC electron density).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The option to study crystal field effects is also considered by Ernst et al (2020). These effects are found to be subtle, as shown previously by Bučinský et al (2019), but important (Ernst et al, 2020). This indicates the capability of XCW to transfer information from structure factors to the XC wavefunction (XC electron density).…”
Section: Introductionmentioning
confidence: 62%
“…In addition, it was shown that XCW is able to account for polarization effects from the crystal environment for the ammonia crystal test case (Bytheway et al, 2002a). The option to study crystal field effects is also considered by Ernst et al (2020). These effects are found to be subtle, as shown previously by Bučinský et al (2019), but important (Ernst et al, 2020).…”
Section: Introductionmentioning
confidence: 72%
“… 4 a/5 b,c: model P minus model G at the QM/MM‐optimized geometry of P ; 4 b/5 e,f: model C minus model G at the QM/MM‐optimized geometry of C ; 4 c/5 h,i: polarization of 1 with a cluster of Hirshfeld‐atom point charges and dipoles (model CC , cluster charges) minus model G at the experimental geometry from X‐ray diffraction; 4 d/5 k,l: effect of X‐ray constrained wavefunction fitting: [22, 28] X‐ray constrained model X minus model G at the experimental geometry from X‐ray diffraction. …”
Section: Resultsmentioning
confidence: 99%
“…4 d/5 k,l: effect of X‐ray constrained wavefunction fitting: [22, 28] X‐ray constrained model X minus model G at the experimental geometry from X‐ray diffraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation